(untitled) (e-Journal of Linguistics, 2023)
This research paper entitled “The Syntax Analysis of Adverb of Manner Found in the Novel “The Wonderful Wizad of Oz”. This research study aimed to analyze the form of adverb of manner and its positions of adverb of manner found in the data source. This research study used the theory proposed by Brown and Miller (1991) in analyzing the tree diagram of adverb of manner and it was supported by other theories in analyzing the form and the position in adverb of manner found in the structure. Library research was the method used in collecting the data as the researcher read the data source before getting data in adverb of manner. The method that was used in analyzing data was qualitative method. The data were taken from the novel entitled “The Wonderful Wizad of Oz” that was written by W.W Denslow. The researcher of this study found that there was one form of adverb of manner found in the novel entitled “The Wonderful Wizad of Oz”. Adverb of manner found in the data source was an adjective followed by ly- suffix. There was one adverb of manner placed in the initial position and eight adverbs of manner placed in final position. They were adverb of manner that could be filled in the sentence structure in the form of adverb of manner